Death, burial and cemeteries in early medieval Chersonese–Cherson: A new book about funeral traditions and ceremony in a provincial Byzantine town. Review on Фомин М. В. Погребальная традиция и обряд в византийском Херсоне (IV–X вв.). – Харьков: Коллегиум, 2011. – 290 с. - Домановський, Андрій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
Фомин М. В. Погребальная традиция и обряд в византийском Херсоне (IV–X вв.) [Funeral Traditions and Ceremonies in the Byzantine Cherson (Fouth to Tenth Centuries)]. – Харьков: Коллегиум, 2011. – 290 с.